Paradigm of Village Physical Activity During Pandemic - Ginting, Ramadan; Lubis, Ade Evriansyah; Nugroho, Agung; Mawardinur, Mawardinur; Sipayung, Dinni Khairiah (ACPES (ASEAN Council of Physical Education and Sport) in cooperation with Universitas Negeri Semarang (UNNES), 2021)
One of the measures to maintain body immunity in the midst of the Covid-19 pandemic is to exercise regularly. The Covid-19 virus was officially declared to have entered Indonesia by the central government since March 2020. The purpose of this research was to find out the differences in the paradigm of physical activity of the residents of Dusun XI, Pond Village, especially those aged 17 years and over, between before the Covid-19 pandemic. 19 and during the Covid-19 pandemic. The research used in the preparation of this scientific article uses quantitative methods which are presented in descriptive form. The paradigm of sports activities for the residents of Dusun XI, Pond Village, which was studied by researchers on a one-week scale, was the intensity of sunbathing, duration of sunbathing, intensity of exercise, duration of exercise, and type of exercise. The research instrument used to measure the physical activity paradigm of residents is the Short-Form version of the Physical Activity Question (PAQ), which is filled out by 50 residents via Google Form. The answers to the questions in the questionnaire which were filled out by the residents of Dusun XI, Pond Village, are the conclusions of this scientific article. The results showed that the paradigm of residents' physical activity that changed after the Covid-19 pandemic was the intensity of sunbathing, the intensity of exercise, and the type of exercise. The Covid-19 pandemic has caused the majority of the residents of Dusun XI of the Pool Village to increase their sunbathing intensity to every day, the majority of the residents of Dusun XI of the Pool Village have decreased their exercise intensity to once a week,